PENGARUH PENGGUNAAN MEDIA GOOGLE CLASSROOM TERHADAP MOTIVASI BELAJAR MAHASISWA PENDIDIKAN EKONOMI FKIP UNIVERSITAS RIAU - Serli Wahyuni; Rr. Sri Kartikowati; Gani Haryana (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: This study aims to describe the Influence of the use of google classroom media on learning motivation of students in Economic Education FKIP, Riau University. This research is a type of quantitative descriptive research, the research population of students of Economics Education FKIP Riau University, batch 2018 and 2019, totaling 149 students. The sampling technique in this study was simple random sampling, with a total sample size of 60 students. Data collection techniques using a questionnaire. Data analysis using simple regression analysis. The results of this study indicates the use of google classroom media has a significant effect on learning motivation.Key Words: Use Of Google Classroom Media, Learning Motivation